Analysis Of Referral System at Maccini Sombala Health Center Based on Human Resources, Medicine Availability, And Service Needs - Nur Akifa Sartika Putri,; Suci Safwa Salsabila, (International Journal Of Health Science, 2025)
The implementation of the referral system from First Level Health Facilities (FKTP) to Advanced Referral Health Facilities (FKRTL) occurs when a health facility faces limitations in resources, such as infrastructure, tools, personnel, or budget. Referrals are also made when patients require specialized care, hospitalization, diagnostic tools, or services that the initial health facility cannot provide, including emergency situations. The BPJS Health annual report on referrals at the Layang Health Center indicates a steady increase in the number of referrals year by year. This study aims to analyze the factors supporting and hindering the referral system, focusing on input and process aspects. The research adopts a qualitative case study approach with 17 informants, including health service employees, center heads, doctors, nurses, pharmacists, laboratory staff, JKN officers, and referred patients. The findings show that human resources at the Layang Health Center are adequate, but there are challenges with the availability of medicines, such as shortages and delays in distribution. Referrals are generally made based on medical needs, but some patients request their own referrals. The center’s health facilities are insufficient, and some essential tools are missing. Although the referral system is based on BPJS Health regulations, its implementation faces obstacles. Patients are often unaware of referral requirements, highlighting the need for better socialization and improved medicine and facility provision to optimize the system.